2021
DOI: 10.1158/1078-0432.ccr-20-2007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of HER Family–targeting Tyrosine Kinase Inhibitors on Antibody-dependent Cell-mediated Cytotoxicity in HER2-expressing Breast Cancer

Abstract: Purpose: Antibody-dependent cell-mediated cytotoxicity (ADCC) is one mechanism of action of the monoclonal antibody (mAb) therapies trastuzumab and pertuzumab. Tyrosine kinase inhibitors (TKIs), like lapatinib, may have added therapeutic value in combination with mAbs through enhanced ADCC activity. Using clinical data, we examined the impact of lapatinib on HER2/EGFR expression levels and natural killer (NK) cell gene signatures. We investigated the ability of three TKIs (lapatinib, afatinib… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 53 publications
3
20
0
Order By: Relevance
“…Further, a substantial inhibition in the total EGFR, HER2, and HER3 levels was observed with neratinib, both alone and even more so in combination with trastuzumab. Our findings are in line with recent preclinical reports showing downregulation of total HER receptor levels in HER2-positive cell models treated with neratinib 32 , 33 . In contrast, with lapatinib alone, the phospho and total HER3 levels were either marginally increased or remained unaffected, potentially suggesting the feedback upregulation of HER3 levels following lapatinib treatment 8 , 34 .…”
Section: Discussionsupporting
confidence: 93%
“…Further, a substantial inhibition in the total EGFR, HER2, and HER3 levels was observed with neratinib, both alone and even more so in combination with trastuzumab. Our findings are in line with recent preclinical reports showing downregulation of total HER receptor levels in HER2-positive cell models treated with neratinib 32 , 33 . In contrast, with lapatinib alone, the phospho and total HER3 levels were either marginally increased or remained unaffected, potentially suggesting the feedback upregulation of HER3 levels following lapatinib treatment 8 , 34 .…”
Section: Discussionsupporting
confidence: 93%
“…However, what would need to be considered is that trastuzumab has several suppression mechanisms of HER2-dependent cell proliferation such as inhibiting HER2-receptor dimerization, preventing the sloughing of the extracellular domain, and immune activation [40]. Upon an immune reaction, some studies demonstrated that breast cancer cells with HER2 low levels resulted in initiating an immune response to breast cancer through the HER2 receptor, and the HER2 protein level was not the only factor indicating the drug response [41,42]. Nevertheless, a further study is required to clarify the mechanism of reaction in cancer with HER2 low expression.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown to outperform other methods in estimating the relative proportion of closely related cell types in bulk tumors without physical cell sorting 12,13 . While the utility of CIBERSORT and CIBERSORTx has been validated in multiple tumor types [14][15][16][17] , their applicability in hematological malignancies remains scarce. A study demonstrated higher fraction of M2 macrophage as a predictor of inferior event-free survival (EFS) and overall survival (OS) in patients with acute myeloid leukemia (AML), and identified the macrophage marker CD206 as a novel prognostic indicator in these patients 18 .…”
Section: Newman Et Al Recently Developed a Computational Method Cibersort (Cell Type Identification Bymentioning
confidence: 99%